Plant growth regulators improve the growth and physiology of transplanted Thalassia Hemprichii fragments - Li, Zhaoyang; Shi, Yunfeng; Zhao, Muqiu; Shi, Zhiqiang; Luo, Huijue; Cai, Jiali; Han, Qiuying (Frontiers in Marine Science, 2024)
Introduction The transplantation of seagrass fragments with shoots and rhizomes is the most common method for the ecological restoration of damaged seagrass meadows. Methods The aim of this study was to explore the effects of exogenous addition (10 mg per month for 3 months) of three commonly used plant growth regulators (PGRs), including indoleacetic acid (IAA), gibberellin (GA3), and paclobutrazol (PP333) on the growth and physiology of transplanted Thalassia hemprichii fragments (TTFs), with and without the rhizome apex (RA), using a simulation test. [Results] IAA and GA3 elevated the photosynthetic capacity and growth rate of TTF leaves but did not significantly alter leaf length and width. In contrast, PP333 reduced the leaf photosynthetic capacity and growth rate, while greatly increasing the leaf width and root viability. Additionally, PP333 treatment led to an increase in antioxidant enzyme activities (peroxidase [POD], superoxide dismutase [SOD], and catalase [CAT]), as well as malondialdehyde (MDA) and total phenol contents in TTFs, indicating some stress effects on the seagrass. Furthermore, IAA and GA3 decreased soluble sugar and protein contents and increased starch content in TTF tissues, whereas PP333 treatment elevated both nonstructural carbohydrate and soluble protein contents. The presence of RA positively affected the growth and physiology of T. hemprichii compared with TTFs without RA. There was a significant interaction between the PGRs and RA on leaf growth rate, chlorophyll fluorescence variables, and photosynthetic pigment content of the TTFs (p < 0.05). Discussion This study provides guidelines for the application of PGRs during the transplantation of T. hemprichii fragments for the restoration of seagrass meadows.